Comparative Analysis of the Impact of Declarative and Imperative Programming Approaches on Android Application Performance Through Benchmarking Method - Nurhadi, Nurhadi; Muslim, Aries (Journal Research of Social Science, Economics, and Management, 2025)
Mobile phones have become essential devices in the digital era, and with Android representing more than 87% of the market share, application performance is a critical factor influencing user retention and business success. Suboptimal performance increases the likelihood of users switching to competing platforms. Accordingly, an in-depth analysis and comparison of available development methods is required to identify the most efficient approach for achieving optimal Android application performance. This study aims to examine the impact of the declarative programming paradigm implemented through Jetpack Compose in comparison with the imperative paradigm using Kotlin-XML on Android application performance. A quantitative method with a benchmarking approach is employed by developing two prototype versions of the IDNFinancials news-portal application to compare and measure the performance of each version. These approaches exhibit distinct characteristics, which should be selected based on development priorities, whether in terms of resource efficiency or the consistency of user experience. The findings of this study are expected to serve as a reference for developers in determining more optimal strategies for implementing Android application interfaces, as well as to contribute to further research on the optimisation of mobile application performance.